Learning impacts reported by students living with learning challenges/disability. Issue 6 (3rd June 2021) - Grimes, Susan; Southgate, Erica; Scevak, Jill; Buchanan, Rachel
ABSTRACT: Internationally, students with disabilities (SWD) are increasing in numbers in higher education institutions. SWD are legally required to be supported by their institutions to ensure equity of access and outcome. Most research around SWD is focused on the provision of support and accommodation to achieve equitable access. Recent research has shown that the majority of students who would qualify as 'disabled' choose not to disclose and receive no support. This research asks SWD ( n = 553) to describe the impact of their disability on their learning. Impacts described included limited access, decreased engagement and cognitive differences. Meeting the needs of these students, who in the main are non-disclosed, is explored through consideration of impairment and disability within the institution with the goal of improving the experience of learning for these students.